Administration de médicaments au nouveau-né par le cathéter ombilical - Gschwind, Liliane; Fonzo-Christe, Caroline; Bonnabry, Pascal; Pfister, Riccardo (Pharmactuel, 2015)
Résumé Objectif : Revue de la catheterisation vasculaire ombilicale et des donnees disponibles concernant l’administration de medicaments par le catheter ombilical veineux (CVO) et arteriel (CAO) en neonatologie. Source des données : Revue de la litterature medicale sur PubMed (1970 a 2011) et consultations d’ouvrages de references pediatriques. Sélection des études et extraction des données : Donnees extraites d’articles de revues, d’enquetes et de rapports de cas. Analyse des données : Le positionnement des CVO et CAO est determinant dans la survenue de complications lors de l’administration de medicaments. Peu de donnees bien etayees sont disponibles. L’evaluation s’est basee sur 22 publications. L’administration de medicaments par CVO est tres frequente en neonatologie, et cette pratique peut etre consideree comme sure a condition que le CVO soit place en position centrale. L’administration de medicaments par le CAO est peu frequente, car elle est plus risquee. De nombreuses complications (vasospasme, thrombose, necrose) ont ete observees a la suite de l’administration de medicaments par CAO. Une position basse du CAO augmente le risque de complications. Conclusion : L’administration de medicaments par CVO ne semble pas poser de probleme sous reserve que le CVO soit correctement positionne (central). L’administration de medicaments par CAO etant risquee, une liste des medicaments pouvant etre ou non administres par CAO (medicaments vasoconstricteurs, irritants ou hyperosmolaires) a ete etablie afin de securiser la prise en charge des patients en neonatologie. Abstract Objective: To review umbilical vascular catheterization and the data available regarding the administration of medication by umbilical venous and arterial catheters (UVC and UAC respectively) in neonates. Data sources: Medical literature review on Pub- Med for the period 1970–2011 and consultation of pediatric references. Study selection and data extraction: Data extracted from review articles, surveys, and case reports. Data analysis: When administering medications, positioning of the UVC and UAC is a determining factor in the occurrence of complications. Few data to support this are available. The evaluation was based on 22 publications. The administration of medication by UVC is common in neonatology, and this practice can be considered reliable under the condition that the UVC is placed in a central position. The administration of medication by UAC is infrequent because it is riskier. Numerous complications (vasospasm, thrombosis, necrosis) have been observed following the administration of medication by UAC. Having the UAC in the low position increases the risk of complications. Conclusion: The administration of medication by UVC does not seem to cause any problems under the condition that the UVC is properly positioned centrally. Given that the administration of medication by UAC is risky, a list of medications that may or may not be administered by UAC (vasoconstrictive drugs, irritants, hyperosmolar substances) was developed to improve the safe management of neonatal patients.